Preparation of nickel-iron hydroxides by microorganism corrosion for efficient oxygen evolution - Huan Yang (Nature Portfolio, 2020)
Developing facile strategies to realize the precise construction of Ni-Fe structures is of significance for water oxidation. Here, the authors demonstrate a universal microorganism-assisted corrosion strategy for preparing highly efficient Ni-Fe composites towards oxygen evolution.